Deficiency of sex hormones does not affect 17-ß-estradiol-induced coronary vasodilation in the isolated rat heart - Santos,R.L. (2016)
The relaxation of coronary arteries by estrogens in the coronary vascular beds of naive and hypertensive rats has been well described. However, little is known about this action in gonadectomized rats. We investigated the effect of 17-ß-estradiol (E2) in coronary arteries from gonadectomized rats, as well as the contributions of endothelium-derived factors and potassium channels. Eight-week-old female and male Wistar rats weighing 220-300 g were divided into sham-operated and gonadectomized groups (n=9−12 animals per group). The baseline coronary perfusion pressure (CPP) was determined, and the vasoactive effects of 10 μM E2 were assessed by bolus administration before and after endothelium denudation or by perfusion with NG-nitro-L-arginine methyl ester (L-NAME), indomethacin, clotrimazole, L-NAME plus indomethacin, L-NAME plus clotrimazole or tetraethylammonium (TEA). The CPP differed significantly between the female and sham-operated male animals. Gonadectomy reduced the CPP only in female rats. Differences in E2-induced relaxation were observed between the female and male animals, but male castration did not alter this response. For both sexes, the relaxation response to E2 was, at least partly, endothelium-dependent. The response to E2 was reduced only in the sham-operated female rats treated with L-NAME. However, in the presence of indomethacin, clotrimazole, L-NAME plus indomethacin or L-NAME plus clotrimazole, or TEA, the E2 response was significantly reduced in all groups. These results highlight the importance of prostacyclin, endothelium-derived hyperpolarizing factor, and potassium channels in the relaxation response of coronary arteries to E2 in all groups, whereas nitric oxide may have had an important role only in the sham-operated female group.